Experimental and Finite Element Evaluation of Long-Term Bond Strength in Alloy-Modified Glass Ionomer Cement - Mohamed Abour (AlQalam Journal of Medical and Applied Sciences, 2026)
To evaluate the long-term effect of alloy addition on the bond strength of glass ionomer cement (GIC) using both experimental testing and finite element analysis (FEA). Glass ionomer cement specimens were modified with 0% (control), 5%, 10%, and 15% alloy content. Shear bond strength was measured at 24 hours, 1, 3, 6, 9, and 12 months. Aging was simulated through water storage. FEA models were developed to simulate stress distribution and predict bond strength over time. Statistical analysis was performed using significance testing (p < 0.05). Alloy addition significantly improved bond strength compared to the control group, with the 10% alloy group demonstrating the highest values at all time points. Experimental results showed a progressive decrease in bond strength over 12 months, with a reduction of up to 54% in the control group. FEA predictions followed similar trends but consistently overestimated bond strength and underestimated long-term degradation. Statistical analysis revealed highly significant differences between control and 10% alloy groups (p < 0.001). Alloy modification enhances both the initial and long-term bond strength of GIC, with 10% alloy providing optimal performance. While FEA effectively predicts trends and material ranking, it requires refinement to accurately simulate long-term degradation.